2016
DOI: 10.1590/1678-4162-9008
|View full text |Cite
|
Sign up to set email alerts
|

Wharton's jelly cells from sheep umbilical cord maintained with different culture media are permissive to in vitro infection by Small Ruminant Lentiviruses

Abstract: This study aimed to isolate cells from the Wharton's jelly of umbilical cord (WJUC) of sheep collected during natural parturition using different culture media, in addition to reporting for the first time the permissiveness of these cells to in vitro infection by small ruminant lentiviruses. Ten umbilical cords were collected from healthy sheep. Each cord explants were grown in different media consisting of MEM, low glucose DMEM, M199, and RPMI-1640. The permissiveness of infection of sheep cells from WJUC was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 13 publications
2
5
0
2
Order By: Relevance
“…In the present study, results from nPCR and Western Blot demonstrated the occurrence of SRLV-positive neonates from mothers infected by these viral agents. These results were confirmed via cell culture, and observation of syncytia and cell destruction, which are some of the main cytopathic effects characteristic of SRLV evidenced in the literature [20,26,32,33].…”
Section: Discussionsupporting
confidence: 72%
See 3 more Smart Citations
“…In the present study, results from nPCR and Western Blot demonstrated the occurrence of SRLV-positive neonates from mothers infected by these viral agents. These results were confirmed via cell culture, and observation of syncytia and cell destruction, which are some of the main cytopathic effects characteristic of SRLV evidenced in the literature [20,26,32,33].…”
Section: Discussionsupporting
confidence: 72%
“…The maternal-filial transmission of SRLV over time has shown strong evidence of its occurrence with tropism to the organs of the reproductive system of goats and umbilical cord cells to this group of retroviruses [19,20]. In the present study, results from nPCR and Western Blot demonstrated the occurrence of SRLV-positive neonates from mothers infected by these viral agents.…”
Section: Discussionsupporting
confidence: 59%
See 2 more Smart Citations
“…The MTT assay was based on the methodology described by Dias et al 43 A cell suspension was prepared at a concentration of 2.0 × 10 5 cells/mL in 12 96-well plates. The samples were then incubated in a CO 2 oven for 24 h. Afterward, the wells were washed with 200 µl sterile PBS-1X at 37 °C.…”
Section: Methodsmentioning
confidence: 99%